Influence of preparation methods on CuO-CeO2 mixed oxide on the oxidation of CO - Huế, Hoàng Thị Hương; Nhiệm, Đào Ngọc (Vietnam Journal of Chemistry, 2014)
Influence of preparation methods (combustion and impregnation) on the oxidation of CO over CuO-CeO2 catalysts has been investigated. Both samples are characterized by means of H2-temperature-programmed reduction (H2-TPR) and Raman spectroscopy. CuO-CeO2 prepared by combustion shows that there are three CuO species in the mixed oxide: the Cu2+ is mostly exist in the CuxCe1-xO2-d solid solution and the left in the bulk CuO and finely dispersed CuO species on the surface of CeO2. CuO-CeO2 prepared by impregnation shows that there are two CuO species in the mixed oxide: the Cu2+ is mostly exist in the finely dispersed CuO species on the surface of CeO2 and the left in the CuxCe1-xO2-d solid solution. The calculating results of the oxygen vacancy concentration in CuO-CeO2 mixed oxide from Gaussian deconvolution of Raman spectra showed that, oxygen vacancy concentration in                                  CuO-CeO2–combustion and CuO-CeO2–impregnation are 12.7 % and 29.7 %, respectively. The catalyst prepared by impregnation is more active for the oxidation of CO, which caused significant differences in the redox properties and the dispersion of copper species. The discrepancies in the dispersion of copper species and the degree of interaction between copper species and ceria determined the reversible redox properties, and consequently the catalytic performance.